Rethinking Cultural Proximity: Transnational Taste Formation Among Indonesian Female Audiences Of Boys’ Love Media - Paramita Winny Hapsari; Dinda Shafira; Iqra Ardini (UNIVERSITAS PAKUAN, 2026)
This study examines how Indonesian female audiences construct cultural proximity toward Boys’ Love (BL) media through transnational exposure rather than local cultural affiliation. Although BL has gained significant popularity in Indonesia through Asian productions, locally produced BL content does not automatically achieve cultural closeness among audiences. This research addresses the gap in cultural proximity studies by questioning the assumption that local media inherently resonates more strongly with local audiences. Using a qualitative case study approach, data were collected through Focus Group Discussions (FGDs) involving two groups of Indonesian women: fans of Asian BL and non-viewers of BL. Participants were exposed to selected clips of Indonesian BL content and invited to share their interpretations, emotional responses, and evaluations. The data were analyzed thematically with cultural proximity as the primary analytical lens, supported by reception theory. The findings reveal that cultural proximity among BL audiences is shaped more by repeated exposure to transnational BL media, particularly from Thailand and Japan, than by national or cultural similarity. BL fans developed transnational taste standards related to narrative style, emotional tone, and production quality, which influenced their evaluation of Indonesian BL content. In contrast, non-viewers tended to rely on local moral and cultural frameworks when interpreting BL media. This study concludes that cultural proximity in the digital media environment is increasingly transnational and affective, suggesting the need to rethink cultural proximity beyond national boundaries in contemporary audience research.